Small-Scale Module of the Rat Granular Retrosplenial Cortex: An Example of the Minicolumn-Like Structure of the Cerebral Cortex - Ichinohe, Noritaka (Frontiers in Neuroanatomy, 2012)
Structures associated with the small-scale module called “minicolumn” can be observed frequently in the cerebral cortex. However, the description of functional characteristics remains obscure. A significant confounding factor is the marked variability both in the definition of a minicolumn and in the diagnostic markers for identifying a minicolumn (see for review, Jones, 2000; DeFelipe et al., 2002; Rockland and Ichinohe, 2004). Within a minicolumn, cell columns are easily visualized by conventional Nissl staining. Dendritic bundles were first discovered with Golgi methods, but are more easily seen with microtubule-associated protein 2 immunohistochemistry. Myelinated axon bundles can be seen by Tau immunohistochemistry or myelin staining. Axon bundles of double bouquet cell can be seen by calbindin immunohistochemistry. The spatial interrelationship among these morphological elements is more complex than expected and is neither clear nor unanimously agreed upon. In this review, I would like to focus first on the minicolumnar structure found in layers 1 and 2 of the rat granular retrosplenial cortex. This modular structure was first discovered as a combination of prominent apical dendritic bundles from layer 2 pyramidal neurons and spatially matched thalamocortical patchy inputs (Wyss et al., 1990). Further examination showed more intricate components of this modular structure, which will be reviewed in this paper. Second, the postnatal development of this structure and potential molecular players for its formation will be reviewed. Thirdly, I will discuss how this modular organization is transformed in mutant rodents with a disorganized layer structure in the cerebral cortex (i.e., reeler mouse and shaking rat Kawasaki). Lastly, the potential significance of this type of module will be discussed.